Self-Assessment in the university context: a systematic review - Beatrice Doria; Valentina Grion (Firenze University Press, 2020)
Assessment is an emerging educational topic and the need to make education a practice aimed at improving university student's learning is growing. The interest in self-assessment as a lifelong learning strategy is also part of this framework. A systematic review of the literature was conducted in order to investigate self-assessment as a learning strategy in the university context and to understand its real benefits. The obtained evidences highlight the positive aspects and the potential of using self-assessment as a learning strategy for university students.   L'autovalutazione nel contesto universitario: una revisione sistematica della letteratura La valutazione risulta un tema emergente in ambito educativo e cresce la necessità di ripensarla come una pratica volta a migliorare l'apprendimento degli studenti universitari. È in tale quadro che si colloca anche l'interesse verso l'autovalutazione come strategia di apprendimento e di lifelong learning. Allo scopo di indagare l'autovalutazione come strategia di apprendimento nel contesto universitario, è stata condotta una revisione sistematica della letteratura con il fine di comprenderne i reali benefici. Le evidenze raggiunte mettono in luce un quadro positivo delle potenzialità di impiego dell'autovalutazione come strategia di apprendimento per gli studenti universitari.